Financing conservation at scale via visitor green fees - von Saltza, Emelia; Kittinger, John N. (Frontiers in Ecology and Evolution, 2022)
Conservation in the Anthropocene requires financing that is commensurate to the scale of threats to ecosystems and the benefits they provide humanity. To meet this challenge, new financing models are needed at a diversity of scales to help support the protection of nature. Visitor green fees – or payments made by visitors to management authorities, for the explicit purpose of funding natural resource management – are an innovative conservation financing tool. In contrast to park fees, these conservation finance systems operate at the scale of an entire jurisdiction, rather than a specific protected area, park or reserve. Despite their recent proliferation worldwide, there is little to no scholarly literature on visitor green fees. In this paper, we assess ten visitor green fee programs worldwide and evaluate their fee system, governance, and management approach. Our over-arching purpose is to explore the challenges and opportunities associated with these conservation financing models, to inform both the evaluation of existing models and to aid practitioners seeking to establish systems to enhance financing for conservation and the ecosystem services that nature provides tourism-dependent destinations.